A ship adrift : governance and development in Bangladesh - International Workshop on Governance and Development (2006 : Dhaka, Bangladesh); Islam, Nurul, 1929-; Asaduzzaman, M. (Dhaka : Bangladesh Institute of Development Studies, 2008)
Revised version of papers presented at the Workshop on Governance and Development, held at Dhaka in November 2006.
Includes bibliographical references.
Keywords: Bangladesh -- Politics and government -- Congresses; Bangladesh -- Economic policy -- Congresses